Lessons learned from case studies of hazardous waste/chemical reactivity incidents. Issue 4 (25th July 2014) - Cox, Brenton L.; Carpenter, Andrew R.; Ogle, Russell A.
<x xml:space="preserve">Abstract</x> The treatment of hazardous waste poses some unique chemical reactivity hazard management challenges. Hazardous waste in the United States is regulated by the Resource Conservation and Recovery Act, typically due to potential environmental and health hazards. However, hazardous waste can also have chemical reactivity hazards associated with storage, handling, or mixing with other materials. The U.S. Environmental Protection Agency has been active in communicating chemical reactivity hazards to the regulated community and has identified numerous sources for additional information. The Center for Chemical Process Safety has also been very active in providing advisory materials and monographs on the safe management of chemical reactivity hazards. Other federal government agencies, such as the Chemical Safety Board and the Occupational Safety and Health Administration, have also taken up the call for increased awareness of the hazards of unintentional chemical reactions. Despite these efforts, history of incidents indicates that reactive chemical hazards associated with hazardous waste still go overlooked. In this article, we review hazardous waste incidents through case studies and public sector reports through the lens of chemical reactivity hazard management. In each incident, inadvertent heating resulted in an unintended chemical reaction, and sufficient information existed or could have been obtained to identify the hazards. © 2014 American Institute of Chemical Engineers Process Saf Prog 33: 395–398, 2014